Electromagnetic methods in petroleum prospecting - STEFANIUK, Michał (Geology, Geophysics and Environment, 2011)
Hydrocarbons saturating rocks give rise to anomalous changes in physical properties of geological medium and measured geophysical fields, thus allowing discovering and recognizing of oil and gas fields. Deposit complexes are characterized by resistivity increased by 1-4 orders of magnitude. Resistivity contrast appear at the lower boundary of deposit, between reservoir rock saturated with mineralized water and saturated with hydrocarbons, as well as at the upper boundary with low-resistivity sealing clayey rocks. Moreover, a contrast of environment's ability to electric polarization induced by electric current flow appears at the boundary between hydrocarbons and formation water. The indirect indicator of a hydrocarbon deposit is the near-surface zone of sulfide mineralization connected with the hydrocarbon diffusion, which modifies magnetic properties and electric polarization ability of the medium. Examples of investigations made in the zone of the Carpathian oil field "Grabownica" and gas field "Rudka" in the Carpathian Foredeep are presented.